PD.04 Development and rapid prototyping of an illuminated mirror for waterbirths – from concept to prototype. (9th June 2014) - Brook-Smith, S; Robson, M; Johnson, N; Lam, A; Leonard, M; Torres-Sanchez, C; Desmulliez, M; Denison, FC
Abstract : Background: Water immersion during labour and birth is recognised as a means of empowering women and reducing need for analgesia. Although waterbirth is a 'hands off' birth, midwives are required to monitor progress and assist controlled delivery of the head. Viewing using a handheld mirror can often be restricted due to maternal position or inadequate lighting, which has implications for infection control and manual handling. There is therefore an unmet clinical need for a mirror with an inbuilt light suitable for use in waterbirths. Objectives: To i) undertake a scoping exercise with midwives and expecting mothers to identify the appropriate product specifications; ii) develop and iii) test prototypes based on these specifications suitable for commercial manufacture. Design pathway and results: Device specification : The device requirements were specified in consultation with midwives of different seniorities attending to their requests and experiences of waterbirths. A novel weekly electronic 'Comic Book' (Figure 1 ) was to facilitate the design process (e.g. nature of illumination, ergonomics of device) and obtain feedback to ensure ongoing engagement with our midwifery target end-users. Prototype development : Schematics and Computer Aided Drawings of potential devices (Figure 2 ) were used to inform the rapid prototyping techniques used to generate a Phase 1 prototype Following Phase I prototype testing and design modification, a Phase 2 prototype was developed which we are currently preparing for licensing Conclusion: Using an innovative and interactive product design process, our multidisciplinary study team have developed an illuminated, flexible prototype mirror for use in waterbirths.